Identification and analysis of hub genes of hypoxia-immunity in type 2 diabetes mellitus - Li, Jing; Yan, Ni; Li, Xiaofeng; He, Shenglin; Yu, Xiangyou (Frontiers in Genetics, 2023)
The chronic metabolic disease named type 2 diabetes (T2D) accounts for over 90% of diabetes mellitus. An increasing number of evidences have revealed that hypoxia has a significantly suppressive effect on cell-mediated immunity, as well as the utilization of glucose in diabetics. Therefore, we aimed to screen and identify hypoxia-immune-related hub genes in T2D through bioinformatics analysis. There were 3822 DEGs and 493 DELs found. After the overlap analysis,38 hypoxia-related DEGs were screened. The functional enrichment analyses revealed that 38 hypoxia-related DEGs were mainly enriched in the GO terms of pyruvate metabolic process, cytoplasmic vesicle lumen and monosaccharide binding, and the KEGG pathways of glycolysis/gluconeogenesis, pentose phosphate pathway and biosynthesis of nucleotide sugars. Moreover, 7 hypoxia-related hub genes were identified by two machine learning algorithms. Immune infiltration analysis suggested that there were 6 cells expressed differently between T2D and healthy samples. Furthermore, AMPD3 and IER3 were screened out through the intersection of 2596 immune-related genes from WGCNA and 7 hypoxia-related hub genes, and the results of the KEGG pathways of genes in high-expression groups of AMPD3 and IER3 were mainly concentrated in glycosaminoglycan degradation and vasopressin-regulated water reabsorption, while the low-expression groups of AMPD3 and IER3 were mainly associated with RNA degradation and nucleotide excision repair. Finally, when compared to normal samples, both the AMPD3 and IER3 were highly expressed in the T2D groups in the GSE184050 and GSE95849 datasets. The result of lncRNA-TF-mRNA regulatory network showed that lncRNAs such as BACH1-IT1 and SNHG15 might induce the expression of the corresponding TFs such as TFAM and THAP12 and up-regulate the expression of AMPD3. Conclusion: This study identified AMPD3 and IER3 as hypoxia-immune-related hub genes and potential regulatory machenism for T2D, which provided a new perspective for elucidating the upstream molecular regulatory mechanism of diabetes mellitus.